Kajian Strukturalisme Dan Nilai Moral Cerita Rakyat Syekh Maulana Manshurudin Cikadueun Sebagai Upaya Pelestarian Dan Bahan Pembelajaran Apresiasi Sastra - Sopyan Sauri (Universitas Mathla'ul Anwar Banten, 2017)
The purpose of this research was to determine the intrinsic elements of folklore and moral values ​​of Sheikh Maulana Manshurudin Cikadueun as the conservation and appreciation of literary learning materials. This research uses qualitatif descriptive method. Analysis of the structure of the story using intrinsic element analysis theory. As for the moral value analysis is based on a combination of several opinions. This research was conducted in the presence of the object of tesearch is Kp Cikadueun, Ds Cikadueun, Kec Cipeucang, Kab Pandeglang. The data used in this study are the data of oral and writing of data. Based on the results of research on folklore Sheikh Maulana Manshurudin Cikadueun can be seen that the structure contained folklore In the story of the people of Sheikh Maulana Manshurudin Cikadueun is the theme, plot, character and characterization, background, viewpoint and mandate. In addition, the results of research shows that moral values ​​contained in the folklore of Sheikh Maulana Manshurudin Cikadueun divided into two: good moral values ​​and bad moral values. Good moral values ​​is religious, responsibility, respect, mutual help, perseverance, love of country, a lot of sense, and courage. While the bad moral values ​​are disobedient to his parents, and lie. Conservation efforts, especially the legend of Sheikh Maulana Manshurudin Cikadueun should continue to be optimized, because it proved that people segitar object of the research have been many who do not know to this folklore. besides the use of folklore Sheikh Maulana Manshurudin Cikadueun as pembelajara material must be done because besides introduction folklore among students in the folklore of these are moral values ​​that can be imitated.